Inovasi media pembelajaran matematika berbasis smart apps creator (SAC) pada materi bangun ruang sisi lengkung - Adelia, Putri; Fitriasari, Putri; Nopriyanti, Tika Dwi (Jurnal Pendidik Indonesia, 2022)
This research is facing background by the frequent us of android as a medium in learning, but there’s no media available in the form of an android application on the curved side space building material. The purpose of this research is to produce a mathematic learning media based on Smart Apps Creator (SAC) on curved sideways material that is valid, practical and has a potential effect on learning outcomes. This research is a type of development research using the ADDIE development procedure. The data of this research were obtained through questionnaries and test. Based on the result of research and data analysis, it can be concluded that the assesment of the questionnaire from the expert obtained a percentage of validity of 95% with very valid criteria. The practicality assessment obtained an average percentage of 89% which means that media is included in the very practical criteria. The potential effect of media on learning outcomes obtained a percentage of 89% with very high criteria.